Divine and Human Hatred in Ancient Egypt - Joseph, Amgad (Journal of ancient Near Eastern religions, 2023)
This article examines the conceptualization of hatred as a complicated and intense emotion in the realms of humans and deities in ancient Egypt. It thoroughly discusses the addressees, psychology, effects, justifications, and incitements of hatred, as well as the possibility of the pacification of its feelings. It discusses the attestations of hatred, its perceived consequences and experience by the deities, living and dead humans. The article also examines the phraseology, contextualization, and lexical semantics of hatred in a detailed lexicographical and linguistic analysis.